Tracing the roots: clarification on the type locality of Halobates sexualis Distant (Heteroptera: Gerridae) - Samuel, Amos Shem (Zootaxa, 2020)
The marine water strider Halobates sexualis Distant, 1903 was originally described from the estuary of Jambu River (Distant 1903). This species has been recorded from Malaysia (Cheng 1985, Zettel & Tran 2009, Ikawa et al. 2012), Sri Lanka (Andersen & Foster 1992, Ikawa et al. 2012) and Thailand (Román-Palacios et al. 2018). In the pioneering work by Herring (1961) on this genus, he mentioned the type locality to be “Estuary of the Jambu River, Malaya.” Andersen and Foster (1992) provided notes on the whereabouts of the type locality of this species and mentioned that it was probably located in northern Malaya (Kuala Jambu) immediately south of the border of Thailand on the Gulf of Siam coast. Andersen and Cheng (2004) further backed this up by mentioning Malaysia in the range of H. sexualis, which was not recorded from Malaysia until 2009 (Zettel & Tran 2009) but also stated that it was not verified personally. However, Distant (1903) mentioned the collection locality as “Estuary of the Jambu River, Jhering.” According to the Map of the Malay Peninsula published around the same time period in 1898 by Stanford, London (RASGBI 1898), Jambu or Jering is located along the coast of Yaring (formerly Jhering/Jering) which is a District Town in Pattani Province of Thailand. This location is about 120 km northwest of the previously presumed location by Andersen & Foster (1992; see fig. 24) and is most likely the site of collection, which is in present-day Thailand. The type locality of this species should thus be attributed to Thailand instead of Malaysia.